2020
DOI: 10.1017/dmp.2019.164
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Pregnant Women Possibly Left Behind in Tsunami Predicted Areas of Nagoya City: A Simulation for Rescue Planning

Abstract: Objective: In case of an outbreak of Nankai Trough Mega-earthquake, it is predicted that a tsunami would invade Nagoya City within 100 minutes, hitting about one third of the City of Nagoya. If the administrative plan of the city and midwives’ expertise are coordinated, pregnant women’s chances of survival will increase. The authors carried out this simulation study in an attempt to improve consistency of the two efforts. Method: We estimated the number of pregnant women using a machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Hattori et al 18 applied data of this study to estimate pregnant women possibly left behind in tsunami predicted areas of Nagoya City. The estimated data of pregnant women were combined with road centerline data 19 in simulating evacuation and rescue plans of the women.…”
Section: Needs Of Simulation For Medical Rescue Teamsmentioning
confidence: 99%
“…Hattori et al 18 applied data of this study to estimate pregnant women possibly left behind in tsunami predicted areas of Nagoya City. The estimated data of pregnant women were combined with road centerline data 19 in simulating evacuation and rescue plans of the women.…”
Section: Needs Of Simulation For Medical Rescue Teamsmentioning
confidence: 99%
“…10 Hattori, et al showed that if Nagoya City were to be hit by a tsunami, more than 1200 pregnant women would not be able to evacuate and would likely be left behind in the tsunami inundation area. 11 Here, we present a method for constructing a simulation of evacuating to a tsunami evacuation building based on data from the city of Nagoya. This includes the following 3 steps:…”
Section: Simulation In Nagoya Citymentioning
confidence: 99%
“…The GIS is not yet very popular among health care workers. Road centerline data improve disaster preparation and planning more effectively 19 ; however, health care workers who have access to use the technique are not onboard. To help resolve this problem, Hattori 20 has developed the GIS training textbook for health care workers.…”
Section: Gis Illiteracymentioning
confidence: 99%